Influence of seasonal changes in daily activity and annual life cycle of Geotrigona mombuca (Hymenoptera, Apidae) in a Cerrado habitat, São Paulo, Brazil - Gobatto,André L. (2013)
The foraging activity of Geotrigona mombuca Smith, 1863 was studied under natural conditions aiming to verify the influence of seasonal changes on daily flight activity and annual cycle of the colony. Daily flight activity was monitored for a year based on the observation and counting of foragers leaving and entering the hive, as well as the kind of material transported and meteorological factors such as day time, temperature and relative humidity. The influence of seasonal changes was evidenced by alterations on daily rhythm of flight activity and by differences on transportation of food resources, building material and garbage. These data indicate that forager behavior is related to daily microclimate conditions and it is synchronized with the requirements of colony annual cycle, which determines an intense pollen collection in the summer. Thus, the recomposition of the intranidal population in spring and summer can be ensured, which is characterized both for a higher intensity of flight activity and increase in garbage and resin transport, as well as the swarming process in the spring. In this way, an action targeting the preservation or management of the species in a natural environment should consider that survival and reproduction of the colony depends greatly on the amount of available pollen in late winter.